Late Bresson and the Visual Arts : Cinema, Painting and Avant-Garde Experiment - Watkins, Raymond (Book collections on Project MUSE., 2018)
Critics have largely neglected the color films of French film director Robert Bresson (1901?99). To correct that oversight, this study presents a revised and revitalized Bresson, comparing his style to innovations in abstract painting after World War II, exploring his affinities with such avant-garde traditions as surrealism, constructivism, and minimalism, and illustrating how his embodied style leads to a complex form of intermediality. Through that analysis, Raymond Watkins shows clearly that Bresson still has a good deal to teach us about cinema?s distinctive ability to draw on painting, photography, sculpture, and the plastic arts in general